PERUBAHAN PENGGUNAAN LAHAN PERTANIAN MENJADI LAHAN NON PERTANIAN DI KECAMATAN SENGAH TEMILA TAHUN 2009-2019 - Utari Aryani; Sulistyarini Sulistyarini; Ludovicus Maditya Hari Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the change in the use of agriculturalland (rice fields) to non-argicultural land (settments) in Sengah Temila sub district in 2009-2019and find out the factors that influence changes in the use of agricultural land (rice fields) to non-agricultural land (settlements) in the district of Sengah Temila. The research method used in this research is descriptive quantitative. The source of the data in the research is Google Earth, SHP data for the administrative map of the Sengah Temila sub district, Landsat image of the year 2009-2019. Data analysis technique using overlay analysis (overlpping), two dimensional matrix analysis, and simple linear regression analysis, the result of this study is that the change in the use of paddy fields to housing is evenly distributed with different levelsof distribution in each village of the Sengah Temila sub district in 2009-2019, the development of the population’shousehold is a factor that influences the change in the us of agricultural land into non-agricultual land in the sub district of Sengah Temila In 2009-2019.